TINJAUAN ATAS PROSEDUR PERHITUNGAN, PEMBAYARAN DAN PELAPORAN PAJAK PENGHASILAN PASAL 21 MENGGUNAKAN METODE NETT PADA PT MYG OLEH KANTOR JASA AKUNTANSI GRACE CONSULT - Atika Aulia Muliawati, (2023)
Taxes are contributions that come from the people and are given to the state. Contributions in question in the form of money, not goods. The company in running it has many obligations that must be fulfilled. One of the obligations is tax. However, not all entrepreneurs do not understand tax administration. This requires Tax Consultant Services in handling corporate taxes. The existence of tax consultant services makes it easier for companies to manage their tax obligations. The purpose of this writer is to find out the procedures for calculating, paying and reporting income tax article 21 using the net method by a tax consultant in Jakarta, namely Grace Consult. Grace Consult is an Accounting Services office registered by the Ministry of Finance of the Republic of Indonesia and has a license as a Tax Consultant of the Republic of Indonesia. The method that the writer uses is descriptive qualitative method. Based on the results of the authors, the procedure for calculating PPh Article 21 on employee salaries is obtained by calculating the entire month's gross income which includes basic salary and allowances, then subtracting the existing deductions, then calculating the year's net income. Then the taxable income (PKP) is calculated, which is equal to one year's net income minus non-taxable income (PTKP). After that, the PKP is multiplied by 5% to get the payable PPh Article 21, then divided by 12 months to get PPh Article 21. Meanwhile, the payment and reporting process is carried out by the employer, treasurer or government cash holder, who pays salaries, and the like. The results of the study can be concluded that the calculation, payment and reporting processes are in accordance with the applicable law.